Sprint cycling performance is maintained with short-term contrast water immersion - Crampton, D.; Donne, B.; Egana, M.; Warmington, S. A. (Medicine & Science in Sports & Exercise, 2011)
Purpose: Given the widespread use of water immersion during recovery from exercise, we aimed to investigate the effect of contrast water immersion on recovery of sprint cycling performance, HR and, blood lactate.